PERAN MODERASI DIVIDEND PAYOUT RATIO TERHADAP HUBUNGAN PROFITABILITAS DENGAN RETURN SAHAM (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI SEKTOR INDUSTRI BARANG KONSUMSI PERIODE TAHUN 2016-2018) - Nailul Mufidah; Indah Yuliana (Jurnal Manajemen, 2020)
This study aims to determine the effect of profitability on stock return and is moderated by the dividend payout ratio (DPR). Stock return is the level of profits obtained by investors on the results of the investment in shares it does. Profitability ratio to measure how much profit the company can get. Indicators of profitability ratios used in the study are return on asset (ROA) and net profit margin (NPM). The dividend payout ratio (DPR) variable is used to see whether it is able to moderate the relationship of profitability to stock returns. The consumer goods industry sector companies listed on the Indonesian Stock Exchange for the period of 2016-2018 were selected as the population used in this study. Purposive sampling technique was used to obtain the number of samples in this study. Based on this technique 13 companies were obtained as samples.Partial least square analysis technique was used in this study. This study shows the results that the higher the value of ROA will affect the rate of return to shareholders, while the NPM has no effect on stock returns, and the DPR is able to moderate the relationship of profitability to stock returns.